2001
DOI: 10.1093/jaoac/84.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 3-Chloro-1,2-Propanediol in Foods and Food Ingredients by Gas Chromatography with Mass Spectrometric Detection: Collaborative Study

Abstract: The results of a collaborative study are reported for the determination of 3-chloro-1,2-propanediol (3-monochloropropane-1,2-diol; 3-MCPD) in a wide range of foods and food ingredients, using gas chromatography with mass spectrometric detection and incorporating the use of a deuterated internal standard. After a pretrial study, 12 laboratories (6 United Kingdom, 1 Switzerland, 1 Japan, 2 United States, 1 The Netherlands, and 1 from the European Commission) were asked to analyze 12 test materials (as known dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Reference materials containing 3-MCPD are commercially available only for soy sauce. The HFBI method has been validated for 3-MCPD in acid-HVP, stocks and soups, soy sauce, salami, fish, cheese, cereals and bread by an international collaborative trial (Brereton et al, 2001). The PBA method has been validated in-house for 3-and 2-MCPD using samples of biscuits, potato crisps, cereals, bread, meat and fish (Wenzl et al, 2015) and found to have good agreement with results obtained with HFBI.…”
Section: Methods Validationmentioning
confidence: 92%
See 3 more Smart Citations
“…Reference materials containing 3-MCPD are commercially available only for soy sauce. The HFBI method has been validated for 3-MCPD in acid-HVP, stocks and soups, soy sauce, salami, fish, cheese, cereals and bread by an international collaborative trial (Brereton et al, 2001). The PBA method has been validated in-house for 3-and 2-MCPD using samples of biscuits, potato crisps, cereals, bread, meat and fish (Wenzl et al, 2015) and found to have good agreement with results obtained with HFBI.…”
Section: Methods Validationmentioning
confidence: 92%
“…Domestic cooking procedures have been shown to increase the levels of 3-MCPD in a limited number of foods studied. The effect is particularly observed in the toasting of bread (Crews et al, 2001;Breitling-Utzmann et al, 2003Hamlet and Sadd, 2004). The increase in the level of 3-MCPD content of bread is greater in brown and wholemeal types.…”
Section: Formation Of Free and Esterified Mcpd And Glycidyl Esters Dumentioning
confidence: 97%
See 2 more Smart Citations
“…These methods suffer from various drawbacks associated with current derivatization schemes. Derivatization with HFBI requires strictly anhydrous conditions (Brereton et al 2001), an excess of PBA is deleterious to the chromatographic system or has to be removed after the reaction (Weisshaar 2008), and aliphatic ketone derivatives lack characteristic molecular ions of the derivatives (Dayrit and Ninonuevo 2004). This last derivatization is usually accomplished using p-toluenesulfonic acid as a catalyst which must be removed from the reaction medium through additional steps.…”
Section: Introductionmentioning
confidence: 99%